Analysis of Translingual Practices: A Case Study of Indonesia Teenagers' Instagram Users - Kusuma, Elinda Dwi; Dharmawan, Yanuarius Yanu; Oktariani S., Alma Indah; Mawuntu, Shany Carolina (Department of English Education, Universitas Panca Sakti Bekasi, 2023)
This research focused on the analysis of the translingual practices of Indonesian teenage Instagram Users based on Muysken’s theory. This research applied the descriptive-qualitative method. The data for this research were the caption posts produced by Indonesian teenagers on Instagram. The sample was taken from Indonesian teenagers’ Instagram users. The data was taken from social media sites such as Instagram. The research also used interviews to learn the reasons why the students produced translingual. The result of this research showed that there were three types of transliteration produced by teenagers. Insertion (noun, verb, preposition, and idiom) and Alternation (phrase and clause), congruent lexicalization based on Muysken’s theory There were some reasons why the students produced code mixing based on Bhatia and Ritchie's theory: participant roles and relationships, situational factors, message-intrinsic factors, language attitude, dominance, and security. The other reasons are to practice their English, to show the group identity, to make it simple and familiar, to show the trend, and to show their personal habits.